Sistem Informasi Akuntansi Pencatatan Penjualan Berbasis Web Pada Bengkel Yuwa Motor - Rezagi Meilano; Rama Dhonal; Riko Sumanto Fredi Nadeak (LP2M Politeknik Jambi, 2023)
Bengkel Yuwa Motor is a service company engaged in repair services. Every cash inflow and outflow transaction activity is recorded into a note and then copied to the Spreadsheet. This can have bad consequences such as delays, miscalculations from data processing actors and inaccurate report results due to data sources that take a relatively long time because the amount of data processed is very large. Therefore, this study discusses the creation of a sales recording system as a software development method consisting of analysis, design, program code creation and testing. Data collection techniques used consisted of observation, interviews and literature study. This cash inflow and cash out information system is expected to help Yuwa Motor Workshop in processing data related to cash in and cash out.